Coefficient estimates for some classes of p-valent functions - M. K. Aouf (International Journal of Mathematics and Mathematical Sciences)
Let Ap, where p is a positive integer, denote the class of functions f(z)=zp+∑n=p+1anzn which are analytic in U={z:|z|<1}.